2022
DOI: 10.3390/v14020411
|View full text |Cite
|
Sign up to set email alerts
|

Elephant Endotheliotropic Herpesvirus 1, 4 and 5 in China: Occurrence in Multiple Sample Types and Implications for Wild and Captive Population Surveillance

Abstract: Elephant endotheliotropic herpesviruses (EEHVs) are important causes of death in both captive and wild Asian elephants (Elephas maximus). Nothing is known about the prevalence of EEHVs in wild or domestic elephants in China. To determine if EEHVs are present in elephants in China, 126 wild elephants from three populations and 202 captive individuals from zoos (n = 155) and the Wild Elephant Valley (n = 47) were screened using semi-nested polymerase chain reaction assays with EEHV-redundant and EEHV1/4/5-specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…Nevertheless, we suggested that long-term engagement in performance might harm the mental health of elephants, leading to stereotypical behavior. Furthermore, since captive elephants in the Wild Elephant Valley were not completely isolated from local wild elephant populations, some pathogens (e.g., EEHVs) carried by captive elephants might spread during their roaming in natural forests and cause the infection of wild individuals (Yang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we suggested that long-term engagement in performance might harm the mental health of elephants, leading to stereotypical behavior. Furthermore, since captive elephants in the Wild Elephant Valley were not completely isolated from local wild elephant populations, some pathogens (e.g., EEHVs) carried by captive elephants might spread during their roaming in natural forests and cause the infection of wild individuals (Yang et al 2022).…”
Section: Discussionmentioning
confidence: 99%
“…A 20-month-old Asian elephant in the UK was euthanized after showing a rapidly progressive disease with severe oedema and haemorrhage in the internal organs [9]. One more EEHV-5 case was reported in a captive elephant in China, which was diagnosed during a prevalence survey on EEHVs in captive animals and wild-life in China [10].…”
Section: Introductionmentioning
confidence: 99%